First report of daratumumab interference in urine immunofixation electrophoresis confirmed by the HYDRASHIFT 2/4 Daratumumab assay - Hyun-Woo Lee; Sooho Yu; Se-Eun Koo; Ghee Young Kwon; Kihyun Kim; Hyung-Doo Park (Annals of Clinical Biochemistry: International Journal of Laboratory Medicine, 2026)
A case of analytical interference in urine immunofixation electrophoresis (IFE) caused by daratumumab is presented. Daratumumab, an IgG1-kappa monoclonal antibody, is well-known to produce a false IgG-kappa band in serum IFE, but urinary interference has not been reported because intact IgG is generally not filtered through the glomerulus. A 67-year-old man presented with nephrotic syndrome and was found to have markedly elevated serum creatinine (3.10 mg/dL), free kappa light chains (453.42 mg/dL) and kappa/lambda ratio (23.23). Baseline serum and urine electrophoresis and IFE showed no monoclonal protein (M-protein), while bone marrow examination confirmed light chain deposition disease with kappa restriction. Following two cycles of daratumumab-based chemotherapy, new IgG-kappa bands appeared in both serum and urine IFE despite improving free light chain levels and unremarkable protein electrophoretic patterns. Suspecting therapeutic antibody interference, the HYDRASHIFT 2/4 Daratumumab assay (HYDRASHIFT assay) was applied to both serum and concentrated urine samples. The IgG-kappa bands in both serum and urine IFE disappeared and exhibited a cathodal shift, confirming that they represented daratumumab rather than endogenous M-protein. This case demonstrates that daratumumab may become detectable in urine in the setting of severely impaired glomerular permeability and highlights that the HYDRASHIFT assay can be effectively applied to urine to resolve analytical interference. Awareness of this phenomenon is important for the accurate interpretation of urine IFE results in patients receiving daratumumab.